Perovskite distributed feedback laser and preparation method thereof
Patent Information
- Application Number
- CN202510556485.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
然而,较差的载流子传输性能和较强的激子-激子淬灭或俄歇(Auger)复合严重制约着有机和量子点电泵浦激光的发展(Nature,1997,389(6649):362-364.)
[0028]与现有技术比较本发明的有益结果:
Smart Images

Figure CN123018551A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of laser technology, and in particular relates to a perovskite distributed feedback laser based on two-beam interference lithography and its fabrication method. Background Technology
[0002] Electrically pumped semiconductor lasers possess advantages such as compact structure, long lifetime, and direct modulation, playing a vital role in manufacturing, medical, communications, and big data fields, and serving as an indispensable supporting technology for national defense and the national economy. With China's development, high-performance, low-cost semiconductor lasers are becoming an increasingly urgent need. While traditional inorganic semiconductor lasers exhibit excellent performance, their complex fabrication processes limit their cost-effective production. Organic semiconductors and quantum dots offer significant optical gain and can be processed using low-cost solution methods. However, their poor carrier transport performance and strong exciton-exciton quenching or Auger recombination severely restrict the development of organic and quantum dot electrically pumped lasers (Nature, 1997, 389(6649):362-364).
[0003] Metal halide perovskite materials, as a new type of semiconductor material, combine many advantages of inorganic and organic semiconductors, such as solution-processable preparation, high gain coefficient, and high carrier mobility. The applicant further explores ways to break through the technical bottlenecks of traditional semiconductor optoelectronic materials and realize high-performance, low-cost electrically pumped semiconductor lasers. Summary of the Invention
[0004] The purpose of this invention is to overcome the above-mentioned shortcomings and provide a perovskite distributed feedback laser based on dual-beam interference lithography technology.
[0005] Another object of the present invention is to provide a method for fabricating the above-mentioned perovskite distributed feedback laser. This method involves fabricating a large-area, high-quality grating on a substrate using two-beam interference lithography, and then fabricating a perovskite thin film on the grating using a solution method to obtain a low-threshold perovskite laser.
[0006] The objective of this invention is achieved through the following means:
[0007] A perovskite distributed feedback laser comprises, from bottom to top, an SU8 photoresist grating and a perovskite emitting layer; the SU8 photoresist grating is prepared by diluting SU8 photoresist and spin-coating it onto a substrate, and then fabricating it using a two-beam interference lithography method.
[0008] Preferably, the substrate is selected from ITO glass or sapphire.
[0009] Preferably, the diluent used for diluting the SU8 photoresist is cyclopentanone, and the volume ratio of SU8 photoresist to cyclopentanone is 1-5:1-20. The method for diluting the photoresist is to mix the SU8 photoresist and cyclopentanone according to the volume ratio, shake well, and let stand for 1-60 minutes to remove air bubbles.
[0010] Preferably, the substrate undergoes pretreatment before spin coating. The pretreatment steps are as follows: the substrate is ultrasonically cleaned sequentially with ethanol and acetone solutions, dried with nitrogen, and then cleaned in a plasma cleaner. This removes residual organic matter from the surface and also increases the wettability of the photoresist on the substrate surface.
[0011] Preferably, the SU8 photoresist grating is prepared by homogenization, pre-baking, exposure, intermediate baking, development, and post-baking.
[0012] Preferably, the SU8 photoresist grating is prepared by the following steps:
[0013] (1) Spin coating: Spin coat SU8 photoresist onto the substrate; the spin coating speed is 4000 rpm, accelerated by 500 rpm, so that the photoresist gradually spreads to the edge of the substrate without generating bubbles, and the duration is 45s.
[0014] (2) Pre-baking: Let the obtained sample stand for 10 minutes, then keep it at 65°C for 5-8 minutes on a hot plate, then keep it at 95°C for 3-5 minutes, and cool it to room temperature; preferably keep it at 65°C for 5 minutes and then keep it at 95°C for 3 minutes.
[0015] (3) Exposure: The obtained sample is exposed on the laser double beam interference optical path to obtain a grating structure. It is preferred that the energy of the two laser beams is adjusted to 0.4mJ and the exposure time is 3-5 seconds. At the same time, gratings with different periods can be obtained by adjusting the angle α between the reflector and the sample on the laser double beam interference optical path.
[0016] (4) Intermediate baking: Hold the grating at 65°C for 5-6 minutes on a hot stage, then hold it at 95°C for 5-6 minutes, and cool it to room temperature to obtain the exposed SU8 adhesive; preferably, hold it at 65°C for 5 minutes and then at 95°C for 5 minutes.
[0017] (5) Development: Immerse the exposed SU8 resin in the developer for 1-2 minutes, and then dry it with nitrogen gas; preferably, the time in the developer is 1 minute.
[0018] (6) Post-baking: Finally, place it on a hot plate at 170°C for 30 minutes to prepare the SU8 photoresist grating.
[0019] The above-mentioned method for fabricating a perovskite distributed feedback laser includes the following steps:
[0020] (1) The diluted photoresist is spin-coated onto the substrate and SU8 photoresist grating is prepared by laser double beam interference lithography. Preferably, an OPO laser with a wavelength of 355nm, a pulse width of 5ns, and a frequency of 10Hz is used for excitation, and the exposure time is 3-5 seconds.
[0021] (2) After cleaning the SU8 photoresist grating in a plasma cleaner for 1 second to 30 minutes, spin-coat the perovskite precursor solution onto the SU8 photoresist grating to obtain a perovskite distributed feedback laser. Plasma cleaning is preferably performed for 10 minutes.
[0022] Preferably, in step (2), an ethanol solution of ZnO is spin-coated onto the cleaned substrate with a DFB grating at a rotation speed of 4000 rpm for 45 s, and then annealed at 150°C for 30 min. The annealed sample is then transferred to a nitrogen glove box, and a perovskite precursor solution is spin-coated onto an SU8 photoresist grating at a rotation speed of 4000 rpm for 4 s. The sample is then placed on a hot stage and kept at 120°C for 10 min to obtain a perovskite distributed feedback laser.
[0023] Preferably, the SU8 photoresist includes SU8-2005 photoresist.
[0024] Preferably, the perovskite precursor solution in step (2) has a mass fraction of 1-50%, more preferably 25%.
[0025] Preferably, in the above scheme, the halogen ratio can be changed by altering the proportions of PbI2, PbBr2, and PbCl2 in the perovskite raw material, thereby achieving tunable emission wavelength of the perovskite laser. The perovskite emitting layer is a perovskite thin film prepared on an SU8 photoresist grating using a solution method. More preferably, the perovskite thin film is perovskite CsPb(I 0.8 Br 0.2 )3 film.
[0026] In this invention, distributed feedback gratings with different periods can be fabricated by adjusting the angle α between the mirror and the sample in the laser dual-beam interference optical path. In perovskite DFB lasers, grating quality significantly affects laser emission; therefore, optimizing a high-quality grating is crucial. Factors such as the pre- and post-baking of the photoresist and exposure time significantly influence grating quality. Furthermore, the collimation, energy, and polarization characteristics of the optical path ensure that the two laser beams have identical polarization and energy, preventing low grating height.
[0027] The aforementioned laser dual-beam interference optical path is constructed as follows: A nanosecond OPO laser, model Radiant HE 355LD, manufactured by OPOTEK (USA), is used as the interference source. The laser beam passes through a half-wave plate and a 355nm beam-splitting cube to achieve continuous adjustment of the laser energy. The shutter is connected to a computer via a USB interface, and LabVIEW programming allows for precise control of the beam's transit time. The beam is then expanded 10 times in diameter using a biconcave lens (-25mm) and a biconvex lens (250mm), and a uniform spot area is selected as the interference spot using an aperture. The laser beam is then passed through a combination of the half-wave plate and the beam-splitting cube, splitting it into two beams with mutually perpendicular polarization directions. The laser energy is continuously adjusted by changing the angle of the half-wave plate, ensuring that the two beams have identical energy. One of the split beams is then passed through a half-wave plate, and its angle is rotated to align its polarization with that of the other beam. Finally, the two beams with identical energy and polarization are reflected onto the sample through two 355nm mirrors for interference.
[0028] The beneficial results of the present invention compared with the prior art are as follows:
[0029] 1. Two-beam interference lithography can achieve large-area adjustable coverage (0.01 mm) at low cost. 2 -1m 2 Patterns can be prepared with adjustable period (100nm-5μm) and adjustable height (1nm-5μm), while the exposure process is simple to operate.
[0030] 2. DFB optical resonators exhibit good wavelength selectivity and relatively high threshold gain, effectively reducing the laser threshold and improving the gain coefficient. Therefore, by adjusting the period of the DFB structure and combining it with a high-quality perovskite thin film, a high-quality (quality factor above 5000) optical resonator can be obtained within the device, thereby achieving a low laser threshold (optically pumped laser threshold reduced to 10 μJ / cm). 2 (The following). The threshold was obtained to be below 50 μJ / cm. 2 It has developed a quasi-continuous perovskite DFB laser and has the potential to realize continuous (CW) lasers and even electrically pumped lasers. Attached Figure Description
[0031] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof. In the drawings:
[0032] Figure 1 This is a schematic diagram of the optical path in a two-beam interference lithography process.
[0033] Figure 2AFM images of high-quality gratings with different periods after system optimization;
[0034] Figure 3 The single-pulse excitation intensity and steady-state PL spectrum of the perovskite DFB laser in Example 1;
[0035] Figure 4 The single-pulse excitation intensity and steady-state PL spectrum of the perovskite DFB laser in Example 2;
[0036] Figure 5 The single-pulse excitation intensity and steady-state PL spectrum of the perovskite DFB laser in Example 3;
[0037] Figure 6 The single-pulse excitation intensity and steady-state PL spectrum of the perovskite DFB laser in Example 4;
[0038] Figure 7 This is a perovskite distributed feedback laser structure.
[0039] Figure 8 An atomic force microscope image of a sample where a poor fabrication process of the comparative grating led to failure of two-beam interference lithography. Detailed Implementation
[0040] The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0041] Example 1:
[0042] A perovskite laser based on dual-beam interference technology has a structure from bottom to top consisting of a transparent substrate ITO glass, a DFB grating, and a perovskite thin film (i.e., a perovskite light-emitting layer).
[0043] 1) Grating fabrication
[0044] a) Diluting the photoresist: Mix SU8-2005 photoresist (purchased from Yilan Microelectronics Co., Ltd.) and diluent (cyclopentanone) at a volume ratio of 1:2, shake well, let stand for 10-20 minutes to remove air bubbles, and set aside.
[0045] b) The transparent substrate ITO glass was ultrasonically cleaned with ethanol and acetone solutions for 10 minutes in sequence, dried with nitrogen, and then placed in a plasma cleaner for 10 minutes. This process removes residual organic matter from the surface and also increases the wettability of the photoresist on the ITO surface.
[0046] c) Spin coating: Spin coat the diluted photoresist onto the substrate at a speed of 4000 rpm, accelerating by 500 rpm, so that the photoresist gradually spreads to the edge of the substrate without generating bubbles, for a duration of 45 seconds.
[0047] d) Pre-baking: Let the spin-coated sample stand for 10 minutes to remove the internal stress caused by the spin coating, then keep it at 65°C for 5 minutes and 95°C for 3 minutes on a hot plate, and then cool it to room temperature to obtain the sample.
[0048] e) Exposure: Exposure is performed on the laser interference optical path. The energy of the two laser beams is adjusted to 0.4 mJ, and the exposure time is 3.5 s to form a grating structure. The laser dual-beam interference lithography optical path is as follows: Figure 1 As shown, by adjusting the angle α between the reflector in the optical path and the sample obtained in step d), grating structures with different periods can be obtained.
[0049] f) Medium baking: Hold at 65°C for 5 minutes on a hot plate, then at 95°C for 5 minutes, and then cool to room temperature.
[0050] g) Development: Immerse the exposed SU8 resin in the developer for 1 minute, and then dry it with nitrogen gas.
[0051] h) Post-baking: Hold at 170°C for 30 min on a hot stage to obtain a distributed feedback (DFB) grating.
[0052] like Figure 2 As shown, a DFB grating structure with a continuously adjustable period range of 400-1000 nm and uniform morphology was finally fabricated. As the angle increases, the grating period becomes smaller and smaller.
[0053] 2) Preparation of perovskite precursor solution:
[0054] Dissolve Zn(Ac)2, CsI, PbI2, PbBr2, and tetraphenylphosphine iodide (TPPI) in N,N-dimethylformamide (DMF) at a molar ratio of 1.5:1.5:0.8:0.2:0.05, with a mass fraction of 25%. Place the solution on a stirring table and stir magnetically until completely dissolved.
[0055] 3) Laser fabrication:
[0056] a) The prepared DFB grating (period 419 nm, height 80 nm) was ultrasonically cleaned with ethanol and acetone solutions for 10 min in sequence, dried with nitrogen, and then placed in a plasma cleaner for 7 min to increase the wettability of perovskite on the grating surface.
[0057] b) Spin-coat an ethanol solution of ZnO onto a cleaned glass ITO substrate with a DFB grating at a spin speed of 4000 rpm for 45 s, and then anneal at 150 °C for 30 min.
[0058] c) Transfer the annealed sample to a nitrogen glove box, and spin-coat 30 μL of the perovskite precursor solution prepared in step 2) onto a DFB grating at a rotation speed of 4000 rpm for 4 seconds. Then place it on a hot stage and maintain it at 120°C for 10 minutes to obtain CsPb(I 0.8 Br 0.2 3. Perovskite DFB laser devices.
[0059] The DFB grating sample was excited using a Radiant HE 355LD OPO laser (5 ns pulse width, 10 Hz frequency) manufactured by OPOTEK Corporation, USA, as the pump source. The spectrum is as follows. Figure 3 As shown, the laser wavelength is 710 nm, the full width at half maximum (FWHM) is 0.79 nm, and the threshold voltage is 0.377 mJ / cm². 2 .
[0060] Example 2:
[0061] The included angle α between the mirror and the DFB grating sample was changed to 24.63°, and the rest of the preparation was carried out according to step 1 in Example 1 to obtain a DFB grating with a period of 426 nm. Then, steps 2 to 3 in Example 1 were repeated.
[0062] The prepared sample was excited using a 355nm OPO laser (5ns pulse width, 10Hz frequency) as the pump source, and the spectrum is as follows. Figure 4 As shown, the laser wavelength is 717.3 nm, the full width at half maximum (FWHM) is 0.55 nm, and the threshold voltage is 0.588 mJ / cm². 2 .
[0063] Example 3:
[0064] 1) Change the angle α between the mirror and the sample to 25.65°, and obtain a DFB grating with a period of 410nm according to step 1 in Example 1.
[0065] 2) Prepare a perovskite precursor solution according to step 2 in Example 1.
[0066] 3) The prepared DFB grating was ultrasonically cleaned with ethanol and acetone solution for 10 min, dried with nitrogen, and then placed in a plasma cleaner for 7 min to increase the wettability of perovskite on the grating surface.
[0067] 4) Spin-coat an ethanol solution of ZnO onto a cleaned glass ITO substrate with a DFB grating at a rotation speed of 4000 rpm for 45 s, and then anneal at 150 °C for 30 min.
[0068] 5) Transfer the annealed sample to a nitrogen glove box, spin-coat 30 μL of perovskite precursor solution onto a DFB grating at 4000 rpm for 45 s, then place it on a hot plate and maintain at 120 °C for 10 min to obtain CsPb(I 0.8 Br 0.2 3. Perovskite DFB laser devices.
[0069] The DFB grating sample was excited using a Radiant HE 355LDOPO laser (5 ns pulse width, 10 Hz frequency) manufactured by OPOTEK Corporation, USA, as the pump source. The spectrum is as follows. Figure 5 As shown, the laser wavelength is 712 nm, the full width at half maximum (FWHM) is 0.58 nm, and the threshold voltage is 0.05 mJ / cm². 2 .
[0070] Example 4:
[0071] The ITO glass substrate was replaced with a sapphire ITO substrate, and the angle α between the reflector and the sample was changed to 26.34°. Following step 1 in Example 1, a DFB grating with a period of 400 nm was obtained on the sapphire substrate.
[0072] Then repeat steps 3 to 6 in Example 3.
[0073] The prepared sample was excited using a 355nm OPO laser (5ns pulse width, 10Hz frequency) as the pump source, and the spectrum is as follows. Figure 6 As shown, the laser wavelength is 706.4 nm, the full width at half maximum (FWHM) is 0.91 nm, and the threshold voltage is 0.139 mJ / cm². 2 .
[0074] Comparative Example 1:
[0075] Grating fabrication: Other conditions are the same as in Example 1-1), except that the pre-baking experimental conditions were changed. In step d), the pre-baking conditions were: 65°C for 4 minutes, 95°C for 1 minute, followed by cooling to room temperature to obtain the sample. The final fabricated grating had issues with insufficient height and grating array distortion. See [link to documentation]. Figure 8 a.
[0076] Comparative Example 2:
[0077] Grating fabrication: The pre-baking, intermediate baking, exposure, and development steps of the photoresist are the same as those in Example 1-1), except that the exposure experimental conditions are changed while other conditions remain the same. The exposure experimental conditions in step e) are: laser energy of 0.4 mJ, and the exposure time is changed to 2.5 s. The final fabricated grating shows visible array distortion. Figure 8 b.
[0078] Comparative Example 3:
[0079] Grating fabrication: The pre-baking, intermediate baking, exposure, and development steps of the photoresist are as described in Example 1-1), except that other conditions remain unchanged, and the intermediate baking time in step f) is changed to: holding at 65°C for 3 minutes on a hot stage, holding at 95°C for 3 minutes, and then cooling to room temperature. The final fabricated grating has problems such as insufficient height and grating array distortion. See [link to example]. Figure 8 c.
[0080] Comparative Example 4:
[0081] Grating fabrication: The pre-baking, intermediate baking, exposure, and development steps of the photoresist are as described in Example 1-1), except that the development time and other experimental conditions are changed. The experimental conditions for step g) are: immersing the exposed SU8 photoresist in the developer for 0.5 min, and then drying it with nitrogen gas. This results in insufficient grating height and grating array distortion in the final fabricated grating, see [link to relevant documentation]. Figure 8 d.
[0082] Depend on Figure 8 It is evident that poor grating fabrication processes can lead to uneven grating distribution, poor grating quality, and negatively impact overall performance.
[0083] The laser dual-beam interference optical path in the above embodiments and comparative examples is constructed as follows: A nanosecond OPO laser, model Radiant HE 355LD, manufactured by OPOTEK, USA, is used as the interference source. The laser beam passes through a half-wave plate and a 355nm beam-splitting cube to achieve continuous adjustment of the laser energy. The shutter is connected to a computer via a USB interface, and LabVIEW programming allows for precise control of the beam's transit time. The beam is then expanded 10 times in diameter using a biconcave lens (-25mm) and a biconvex lens (250mm), and then a uniform spot area is selected as the interference spot using an aperture. The laser beam is then passed through a combination of a half-wave plate and a beam-splitting cube, splitting the beam into two beams with mutually perpendicular polarization directions. The laser energy is continuously adjusted by changing the angle of the half-wave plate, ensuring that the two beams have identical energy. One of the split beams is then passed through a half-wave plate, and its angle is rotated to align its polarization with that of the other beam. Two beams of light with identical energy and polarization are then reflected onto the sample through two 355nm mirrors to induce interference. (See...) Figure 1 .
Claims
1. A perovskite distributed feedback laser, characterized in that... The perovskite laser comprises, from bottom to top, an SU8 photoresist grating and a perovskite light-emitting layer; the SU8 photoresist grating is prepared by diluting SU8 photoresist and spin-coating it onto a substrate, and then fabricating it using a two-beam interference lithography method.
2. The perovskite distributed feedback laser according to claim 1, characterized in that... The substrate is selected from ITO glass or sapphire.
3. The perovskite distributed feedback laser according to claim 2, characterized in that... The diluent used for diluting the SU8 photoresist is cyclopentanone, and the mixing volume ratio of SU8 photoresist and cyclopentanone is 1-5:1-20.
4. The perovskite distributed feedback laser according to claim 2, characterized in that... The substrate is pretreated before spin coating. The pretreatment steps are as follows: the substrate is ultrasonically cleaned with ethanol and acetone in sequence, dried with nitrogen, and then placed in a plasma cleaner for cleaning.
5. The perovskite distributed feedback laser according to claim 1, characterized in that... The SU8 photoresist includes the SU8-2005 type.
6. The perovskite distributed feedback laser according to claim 1, characterized in that... The perovskite emitting layer is a perovskite thin film prepared on an SU8 photoresist grating using a solution method.
7. The perovskite distributed feedback laser according to claim 1, characterized in that... The SU8 photoresist grating is prepared by homogenization, pre-baking, exposure, intermediate baking, development and post-baking.
8. The perovskite distributed feedback laser according to claim 7, characterized in that... The SU8 photoresist grating is prepared by the following steps: (1) Spin coating: Spin coat SU8 photoresist onto the substrate; the spin coating speed is 4000 rpm, accelerated by 500 rpm, so that the photoresist gradually spreads to the edge of the substrate without generating bubbles, and the duration is 45s. (2) Pre-baking: Let the obtained sample stand for 10 minutes, then keep it at 65°C for 5-8 minutes on a hot plate, then keep it at 95°C for 3-5 minutes, and cool it to room temperature; (3) Exposure: Expose the obtained sample on the laser double-beam interference optical path to obtain a grating, with an exposure time of 3-5 seconds; (4) Intermediate baking: Hold the grating at 65°C for 5-6 minutes on a hot stage, then hold it at 95°C for 5-6 minutes, and cool it to room temperature to obtain the exposed SU8 adhesive. (5) Development: Immerse the exposed SU8 resin in the developer for 1-2 minutes, and then dry it with nitrogen gas; (6) Post-baking: Finally, place it on a hot plate at 170°C for 30 minutes to prepare the SU8 photoresist grating.
9. A method for fabricating the perovskite distributed feedback laser according to claim 1, characterized in that... The method includes the following steps: (1) The diluted photoresist was spin-coated onto the substrate, and the SU8 photoresist grating was prepared by laser double-beam interference lithography. (2) After cleaning the SU8 photoresist grating in a plasma cleaner for 1 second to 30 minutes, spin-coat the perovskite precursor solution onto the SU8 photoresist grating to obtain a perovskite distributed feedback laser.
10. The method for fabricating a perovskite distributed feedback laser according to claim 9, characterized in that... The perovskite precursor solution in step (2) has a mass fraction of 1%-50%.
